(untitled) (Journal of Advanced Veterinary and Animal Research, 2014)
This study was conducted to determine the prevalence of ticks infesting cattle and seroprevalence of Theileria annulata antibodies in White Nile State, Sudan between March to June 2012. Ticks, blood smears (n=105) and serum samples (n=82) were collected from Rabak, Kosti, El Dowaim, El Getaina, El Jabalain, Kenana and El Gezira Aba. Three tick genera and eleven species were identified. The genera belong to Amblyomma, Hyalomma and Rhipicephalus. The species were A. lepidum (810), A. variegatum (7), H. impeltatum (189), H. truncatum (78), H. anatolicum (255), H. dromedarii (19), H. rufipes (338), R. (Boophilus) decoloratus (54), R. (B.) annulatus (56), R. evertsi evertsi (476) and R. sanguineus group (60). Out of 105 blood smears, 7 (6.7%) were positive for Theileria spp. piroplasms, whereas in ELISA, out of 82 serum samples, 50 (61%) were positive for T. annulata antibodies. It is concluded that there are three tick genera and eleven species infesting cattle in White Nile State and the high prevalence T. annulata antibodies indicates that tropical theileriosis is endemic in the region. Prevalence of Amblyomma spp. implying that heartwater may be endemic in the area. http://dx.doi.org/10.5455/javar.2015.b53